Withdrawal of inhaled steroids in children with non-cystic fibrosis bronchiectasis - KARADAĞ, BÜLENT TANER; GÜRAN, TÜLAY (WILEY, 2008)
To study the effects of inhaled steroid withdrawal on bronchial hyperreactivity, sputum inflammatory markers and neutrophilic apoptosis in children with non-cystic fibrosis (non-CF) bronchiectasis. To evaluate the role of inhaled steroids in the treatment of children with non-CF bronchiectasis with specific emphasis on the bronchial hyperreactivity and neutrophilic apoptosis. Twenty-seven children with steady-state non-CF bronchiectasis were evaluated primarily with metacholine challenge tests and apoptotic neutrophil ratios in induced sputum and secondarily with symptom scores, pulmonary function tests and tumour necrosis factor-alpha (TNF-alpha), interleukin-8 (IL-8) levels and neutrophil ratios in induced sputum before and after 12-week withdrawal of inhaled steroids. There were 16 girls and 11 boys. Median (interquartile range) age was 11.4 (9.5-13.6) years, follow-up duration was 3.5 (2-6.5) years. Symptom scores (4 vs. 3; P = 0.27), oxygen saturation (95% vs. 97%; P = 0.06), pulmonary function tests (FEV1: 82% predicted vs. 83% predicted; P = 0.73), sputum neutrophil ratios (29.9% vs. 46.8%; P = 0.20), TNF-alpha (58 pg/mL vs. 44.5 pg/mL; P = 0.55) and IL-8 (2.7 ng/mL vs. 2.4 ng/mL; P = 0.82) levels in induced sputum were similar before and after 12-week withdrawal of inhaled steroids. However, the number of patients with bronchial hyperreactivity increased (37% vs. 63% of patients; P = 0.016) and neutrophilic apoptosis in induced sputum decreased (42.8% vs. 20.2%; P = 0.03) after withdrawal. In this study, 12 week-withdrawal of inhaled steroid treatment resulted in a significant increase in bronchial hyperreactivity and decrease in neutrophil apoptosis, but no change in sputum inflammatory markers in children with non-CF bronchiectasis was observed.
Keywords: apoptosis; bronchial hyperreactivity; bronchiectasis; children; interleukin-8; induced sputum; tumour necrosis factor-alpha; AIRWAY RESPONSIVENESS; INDUCED SPUTUM; LUNG-FUNCTION; BRONCHIAL HYPERREACTIVITY; FLUTICASONE PROPIONATE; INFLAMMATORY INDEXES; NEUTROPHIL APOPTOSIS; ASTHMA; METHACHOLINE; HYPERRESPONSIVENESS